THE DEPENDANCE OF RESISTANCE IN RESPIRATORY INFECTIONS, VITAMIN D DEFICIENCY AND ACADEMIC ACHIEVEMENT ON PHYSICAL ACTIVITY OF STUDENTS - Абрамова, Наталья; Syed, Mohammed (SWorldJournal, 2021)
Problems arising in the process of educational activities related to physical and mental health, adaptation of students to the conditions of study, improving efficiency, drawing up a proper schedule taking into account the workload, research activities, a